The Unique Position of National Human Rights Institutions: A Mixed Blessing? - Smith, Anne
"National Human Rights Institutions can play a key role in promoting and protecting human rights. They are able to do so by the unique position they occupy between government, civil society, and nongovernmental organizations (NGOs). However, this unique position which holds out opportunities for national human rights institutions also gives rise to problems for such institutions. National human rights institutions have to define and defend their role or space in relation to where they fit in with government and civil society."
Keywords: DERECHOS HUMANOS; PROMOCION DE LOS DERECHOS HUMANOS; PROTECCIÓN DE LOS DERECHOS FUNDAMENTALES